2017
DOI: 10.7196/samj.2017.v107i4.12084
|View full text |Cite
|
Sign up to set email alerts
|

Wound infection secondary to snakebite

Abstract: Background. Snakebites can produce severe local and systemic septic complications as well as being associated with significant overall morbidity and even mortality. Objective. A prospective audit was undertaken to determine the bacterial causation of wound infection secondary to snakebite, and attempt to quantify the burden of disease. Methods. The audit was undertaken at Ngwelezane Hospital, which provides both regional and tertiary services for north-eastern KwaZuluNatal Province, South Africa, over a 4-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 18 publications
(29 reference statements)
5
61
0
Order By: Relevance
“…From a clinical perspective, identification of E. faecalis as the most prevalent culturable microbe 20 across our European N. nigricollis venom samples strikingly reflects three independent clinical reports across Africa and Asia that this non-sporulating microbe is the most common Gram positive infection cultured from infected envenomation wounds (Mao et al 2016;Lam et al 21 2011;Wagener et al 2017). Further epidemiological data from countries with high envenomation incidence (Mao et al 2016;Lam et al 2011;Wagener et al 2017;Johnston et al 2017;Monteiro et al 2002) challenge the consensus view in developed nations that venom is sterile, opportunistic primary infection upon envenomation is uncommon, and that venom wound infection is a consequence of poor hygiene or poor debridement practice (Talan et al 1991;5 Powers 2005). Accordingly, in an experimental rabbit model of dermonecrosis (Monteiro et al 2002) caused by Loxosceles intermedia (recluse spider) venom, Clostridium perfringens recovered from the spider fang and venom enhanced disease symptoms.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…From a clinical perspective, identification of E. faecalis as the most prevalent culturable microbe 20 across our European N. nigricollis venom samples strikingly reflects three independent clinical reports across Africa and Asia that this non-sporulating microbe is the most common Gram positive infection cultured from infected envenomation wounds (Mao et al 2016;Lam et al 21 2011;Wagener et al 2017). Further epidemiological data from countries with high envenomation incidence (Mao et al 2016;Lam et al 2011;Wagener et al 2017;Johnston et al 2017;Monteiro et al 2002) challenge the consensus view in developed nations that venom is sterile, opportunistic primary infection upon envenomation is uncommon, and that venom wound infection is a consequence of poor hygiene or poor debridement practice (Talan et al 1991;5 Powers 2005). Accordingly, in an experimental rabbit model of dermonecrosis (Monteiro et al 2002) caused by Loxosceles intermedia (recluse spider) venom, Clostridium perfringens recovered from the spider fang and venom enhanced disease symptoms.…”
Section: Discussionmentioning
confidence: 53%
“…Yet over three quarters of snake bite victims may develop mono-or polymicrobial envenomation wound infections, characterized by Bacteroides, 15 Morganella, Proteus, and Enterococcus (Wagener et al 2017;Mao et al 2016) -bacterial taxa commonly found in the gut. Indeed, Enterococcus faecalis and Morganella morganii have been independently reported as the most common Gram positive and Gram negative infections across several countries (Mao et al 2016;Lam et al 2011;Wagener et al 2017). Historically associated with the oral snake microbiome (Jorge et al), these bacteria are thought to originate from prey 20 faeces (Garg et al 2009) persisting in the snake oral cavity (Lam et al 2011) with a diversity similar to that of the snake gut (Iqbal et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 5 million snake bites are estimated to occur annually, the majority occurring in Africa and southeast Asia [103]. Infections after a snakebite have been reported to affect 9%-35% of victims [106,107].…”
Section: Necrotizing Soft Tissue Infectionsmentioning
confidence: 99%
“…The administration of antibiotics is recommended by the World Health Organization (WHO) for snakebite victims, with the purpose of preventing sepsis or necrosis, or avoiding secondary infection when the bite wound has obviously been tampered with [1]. Antibiotics are also sometimes administered prophylactically to snakebite victims, even under conditions different from those recommended by the WHO [2][3][4]. This study aims at investigating, for the first time, the effect of antibiotics on snake venom toxins.…”
Section: Introductionmentioning
confidence: 99%